Acute gluten-induced inflammatory response highlights CCL20 as a potential biomarker for celiac disease - Gómez-Aguililla, Sara; Farrais, Sergio; López-Palacios, Natalia; Arau, Beatriz; Senosiain, Carla; Infante-Menéndez, Jorge; Ruiz-Carnicer, Ángela; Fernández-Bañares, Fernando; González-López, Nuria; Pujals, Mar; Sousa, Carolina; Núñez, Concepción (Frontiers in Immunology, 2026)
BackgroundDiagnosis of celiac disease (CD) remains challenging in individuals already on a gluten-free diet (GFD). Although several alternative methods have been proposed, they have limitations. Identifying inflammation-related proteins that rapidly respond to gluten exposure in blood may offer diagnostic alternatives. We aimed to characterize the inflammatory protein response to gluten in patients with CD on a GFD, and to assess the diagnostic potential of candidate biomarkers and their association with clinical symptoms.MethodsSeventeen patients with CD and 15 non-CD individuals on a GFD (≥ 1 month) consumed 10 g of gluten. Serum, plasma and clinical symptoms were collected at baseline and 4 h post-gluten ingestion to assess changes in 92 inflammation-related proteins. CCL20 levels were also measured by ELISA in plasma from 13 patients with CD and 11 non-CD individuals from the initial cohort, and in an additional group of 28 individuals evaluated for suspected CD, three of whom received a final diagnosis of CD. In 15 patients with CD, the results were compared to those of other diagnostic approaches.ResultsTwelve proteins showed significantly different fold changes following gluten challenge between CD and non-CD groups. Six showed an AUC ≥80%, and CCL20 achieved 81.3-85.7% sensitivity and 88.9-92.7% specificity for CD diagnosis. CCL20 level increases post-gluten challenge were higher in patients with vomiting but were also observed in those with absent or mild symptoms.ConclusionGluten reintroduction triggers alterations in the inflammation-related protein profile of patients with CD. CCL20 emerges as a promising diagnostic candidate, its increase in plasma or serum, with low dependence on symptom presentation, may complement existing diagnostic approaches.